PENGARUH CASH POSITION, DEBT TO EQUITY RATIO, RETURN ON ASSET, ASSET GROWTH DAN FIRM SIZE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2014-2015 - -, Dodi Susanto (EKONOMIA, 2018)
Dodi Susanto: Effect of Cash Position, Debt To Equity Ratio, Return on Assets, Asset Growth, and Firm Size on Stock Prices in Manufacturing Companies in the Indonesia Stock Exchange for the 2014-2015 period. Under the guidance of Mr. Robin Jonathan and Mrs. Ivana Nina Esterlin Barus.This research was conducted to determine the effect of cash position, debt to equity ratio, return on assets, asset growth, and firm size on stock prices in manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2015 period, both partially and simultaneously.The analysis used is ratio analysis, research instrument test in the form of classic assumption test, multiple linear regression analysis, and hypothesis testing including multiple determination coefficient test, t statistical test, and F. statistical test.From the results of simultaneous calculations, all variables of cash position, debt to equity ratio, return on assets, asset growth, and firm size have a significant effect on the stock price of manufacturing sector companies listed on the Stock Exchange in 2014-2015.From the results of the calculation, the results obtained that cash position, debt to equity ratio, and asset growth have a negative and insignificant effect on the stock price of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2015 period. While the variable return on assets and firm size has a positive and significant effect on the stock price of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2015 period.Â